Identification damage model for thermomechanical degradation of ductile heterogeneous materials - El Amri, Abdelouahid; Khamlichi, Abdellatif; El Yakhloufi, Mounir Haddou (Zielona Góra: Uniwersytet Zielonogórski)
The failure of ductile materials subject to high thermal and mechanical loading rates is notably affected by material inertia. The mechanisms of fatigue-crack propagation are examined with particular emphasis on the similarities and differences between cyclic crack growth in ductile materials, such as metals, and corresponding behavior in brittle materials, such as intermetallic and ceramics. Numerical simulations of crack propagation in a cylindrical specimen demonstrate that the proposed method provides an effective means to simulate ductile fracture in large scale cylindrical structures with engineering accuracy. The influence of damage on the intensity of the destruction of materials is studied as well.
Keywords: damage; manufacturing; thermal fatigue; mechanical fatigue